The Influence of Green Products and Green Marketing on Consumer Purchase Decisions in Medan Tembung Culinary MSMEs: Pengaruh Green Product dan Green Marketing terhadap Keputusan Pembelian konsumen pada UMKM Kuliner Medan Tembung - Carine; Afrizal; Jupert Jasser Abellana; Jessa Labitad (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study aims to analyze the influence of green products and green marketing on consumer purchase decisions in culinary MSMEs in Medan Tembung District. The background of the research is based on the low understanding of MSME actors on the importance of implementing environmentally sound strategies in attracting consumers. The research method used a descriptive quantitative approach by distributing questionnaires to 305 respondents through incidental sampling techniques. The data were analyzed using validity, reliability, and multiple linear regression tests with the help of SPSS 25. The results of the study show that green products and green marketing have a positive and significant effect, both partially and simultaneously, on consumer purchase decisions. This emphasizes that the success of culinary MSMEs is not only determined by the quality of taste and price, but also by a commitment to sustainability practices. The practical implication of this study is the need for MSMEs to strengthen green product strategies through the use of local raw materials, environmentally friendly packaging, and emphasizing green marketing with effective communication on social media to increase competitiveness and consumer loyalty.